(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article analyzes the analysis of scientific approaches that illuminate the content and essence of the psychological factors of the manifestation of emotional distress in students of higher education institutions. As well as there are practical recommendations for the organization and conduct of psychological correctional measures to overcome emotional distress in students.